2015
DOI: 10.1007/s00436-015-4879-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of biogenic carbon dioxide produced by yeast with different carbon sources for attraction of mosquitoes towards adult mosquito traps

Abstract: Surveillance is a prime requisite for controlling arthropod vectors like mosquitoes that transmit diseases such as malaria, dengue and chikungunya. Carbon dioxide (CO2) is one of the main cues from vertebrate breath that attracts mosquitoes towards the host. Hence, CO2 is used as an attractant during surveillance of mosquitoes either from commercial cylinders or dry ice for mosquito traps. In the present study, the biogenic carbon dioxide production was optimized with different carbon sources such as glucose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…This is the case of fungal partners, and more particularly yeasts, which produce CO 2 and volatile secondary metabolites as by-products during fermentation that attract many insects including mosquitoes [33,[71][72][73]. In addition to the presence of VOCs, it was demonstrated that CO 2 produced by yeasts during fermentative metabolism of different carbon sources attracts significantly more mosquitoes than industrial CO 2 or octenol (fungal aromatic compound) used alone [74][75][76][77]. However, according to the mosquito species, the nature of the VOCs and their concentration, mosquitoes can be attracted as well as repelled [73].…”
Section: Attractive or Repulsive Effects And Impact On Breeding Site mentioning
confidence: 99%
“…This is the case of fungal partners, and more particularly yeasts, which produce CO 2 and volatile secondary metabolites as by-products during fermentation that attract many insects including mosquitoes [33,[71][72][73]. In addition to the presence of VOCs, it was demonstrated that CO 2 produced by yeasts during fermentative metabolism of different carbon sources attracts significantly more mosquitoes than industrial CO 2 or octenol (fungal aromatic compound) used alone [74][75][76][77]. However, according to the mosquito species, the nature of the VOCs and their concentration, mosquitoes can be attracted as well as repelled [73].…”
Section: Attractive or Repulsive Effects And Impact On Breeding Site mentioning
confidence: 99%
“…Carbon dioxide has been repeatedly reported as essential in combination with an odour blend for attracting host-seeking malaria vectors (55)(56)(57) and remains one of the most challenging obstacles to area-wide operational use of odour-baited traps. Carbon dioxide gas released from cylinders is not manageable under eld conditions; hence a previously developed method of producing CO 2 from fermenting sugar or molasses solution using yeast is now widely used (58)(59)(60). However, the amount of sugar or molasses needed for every trap night is still prohibitive for operational vector control.…”
Section: Suna Trap and Odour Lure (Pull Component)mentioning
confidence: 99%
“…Therefore, this study evaluated different olfactory and physical cues to identify suitable attractants for the designed POHD ( Figure 2 ). The sources of olfactory cues were the Ifakara blend [ 18 ], Mbita blend [ 16 ], BG lure [ 17 ], the yeast-produced CO 2 [ 10 , 52 , 53 ], and human worn socks [ 19 ]. The socks were worn by a male volunteer of 24 years old for 12 hours to collect human skin odors as a source of attractants.…”
Section: Methodsmentioning
confidence: 99%
“…The socks were worn by a male volunteer of 24 years old for 12 hours to collect human skin odors as a source of attractants. The fermented produced CO 2 was generated from a mixture of fermented yeast and sugar solution as described elsewhere [ 10 , 52 , 53 ]. Another software of designed POHD was the physical attractants such as heat and light sources.…”
Section: Methodsmentioning
confidence: 99%